2015
DOI: 10.4236/ojmm.2015.54031
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Multi-Drug Resistant <i>Klebsiella pneumonia</i> and Other Gram Negative Bacteria in Neonatal Sepsis in Equatorial Guinea

Abstract: The study was conducted on new-born babies in whom septicemia was suspected, to determine the prevalence of bacterial strains isolated and their sensitivity to antimicrobial drugs. The study was carried out at La Paz Medical Center, Microbiology section, Malabo, Equatorial Guinea from August 2013 to October 2015. Out of 293 septicemia suspected cases, 29 (10%) blood cultures were positive, 28 with bacterial growth and 1 with growth of Candida sp. The mortality rate of neonates caused by Gram negative bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 8 publications
4
14
0
Order By: Relevance
“…Only few studies reported use of Etest 72,73,106,107 or microdilution 59 on all or some isolates. Several established guidelines for resistance interpretation were referenced: Clinical and Laboratory Standards Institute (CLSI; 36 stu dies), 24,31,36,56,59,63,70,72,73,84,[86][87][88]93,96,99,103,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] EUCAST, 107 British Society for Antimicrobial Therapy, 60,61,71,97 and French Society of Microbiology. 91 Only 12 (15%) of 81 observational studies provided context by describing the pathway of neonatal presentation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only few studies reported use of Etest 72,73,106,107 or microdilution 59 on all or some isolates. Several established guidelines for resistance interpretation were referenced: Clinical and Laboratory Standards Institute (CLSI; 36 stu dies), 24,31,36,56,59,63,70,72,73,84,[86][87][88]93,96,99,103,106,[108][109][110][111][112][113][114][115][116][117][118][119][120][121][122][123][124][125] EUCAST, 107 British Society for Antimicrobial Therapy, 60,61,71,97 and French Society of Microbiology. 91 Only 12 (15%) of 81 observational studies provided context by describing the pathway of neonatal presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Only 13 (16%) of 81 studies listed pathogens excluded as contaminants. Although often reported as contaminants, several studies reported CoNS, 24,34,38,55,71,74,86-89,96,98,103,106,109,111-113,115-118,120,126-132 viridians streptococci, 61,85 Staphylococcus epidermidis, 84,99,125,133,134 Bacillus spp, 106,130 and Micrococcus spp 122 as neonatal pathogens. However, among the studies that reported CoNS as a pathogen, few provided a rationale for identifying the clinical significance of the infection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations